Prevalence of sun protection behaviors in Hispanic youth residing in a high ultraviolet light environment. Issue 1 (21st November 2017) - Altieri, Lisa; Miller, Kimberly A.; Huh, Jimi; Peng, David H.; Unger, Jennifer B.; Richardson, Jean L.; Allen, Martin W.; Cockburn, Myles
Abstract: Although rates of late‐stage melanoma are rising in Hispanics, particularly those living in high ultraviolet light environments, little is known about the prevalence of sun protective behaviors in Hispanic children. We analyzed baseline data including frequency of sunburn, sun protective behaviors, level of U.S. acculturation, and skin phototype from a cross‐sectional survey of 2003 Hispanic elementary school children in Los Angeles, California, who participated in a skin cancer prevention intervention. Although the Hispanic children reported frequently engaging in some sun protective behaviors, they also had a high rate of sunburn (59%) that exceeded previous national estimates for non‐Hispanic white children (43%). Fewer U.S.‐acculturated children reported more frequent shade‐seeking at home ( P = .02), along with less shade‐seeking at school ( P = .001) and more sunscreen use at school ( P = .02). The surprisingly high rate of sunburn in Hispanic children suggests that the way in which they are practicing sun protection is not preventing sunburns. Sun safety interventions should be targeted toward Hispanic youth to provide them with practical methods of effective sun protection, in addition to education on the risks of high sun exposure.